Factors influencing treatment duration of oral propranolol in infantile hemangioma: a five-year retrospective analysis - Li, Qian; Xiao, Liu; Su, Mengting; Chen, Hongguang; Zhang, Haihua; Cao, Nana; Jiang, Lixiao; Liu, Xiaoyan; Zhang, Gaolei (Frontiers in Pediatrics, 2026)
BackgroundOral propranolol is effective in promoting the involution of infantile hemangiomas (IHs), but treatment outcomes vary widely.ObjectivesTo identify demographic and clinical factors influencing the time to achieve complete regression in IH patients treated with propranolol.MethodsA retrospective study was conducted on 410 IH patients treated at the Department of Dermatology and Venereology, Capital Center for Children's Health, Capital Medical University, between 2018 and 2023. Patients received propranolol (3 mg/kg/day) and were followed monthly. The primary outcome was the time (months) required to achieve an Achauer grade IV response, defined as complete or near-complete resolution. Treatment was continued until this endpoint was reached.ResultsThe cohort included 157 males (38.3%) and 253 females (61.7%) with a median age of 2 months (interquartile range, 2–4 months); 36 (8.8%) were preterm. All patients eventually achieved an Achauer IV outcome, with a median treatment duration of 7 months (95% CI, 6–10 months). Age at treatment initiation, lesion location, and IH subtype significantly influenced the time to cure, while sex and prematurity did not.ConclusionsPropranolol remains the first-line pharmacotherapy for IHs. The treatment duration required to reach an Achauer IV outcome is prolonged when therapy begins after 7 months of age, when lesions are located in the periorbita, nose, chest/back, perineum/anal region, or when deep/mixed subtypes are present.